Amelioration of Cognitive Deficit by Embelin in a Scopolamine-Induced Alzheimer’s Disease-Like Condition in a Rat Model - Bhuvanendran, Saatheeyavaane; Kumari, Yatinesh; Othman, Iekhsan; Shaikh, Mohd Farooq (Frontiers in Pharmacology, 2018)
Embelin (2,5-dihydroxy-3-undecyl-1,4-benzoquinone) is one of the active components (2.3%) found in Embelia ribes Burm fruits. As determined via in vitro AChE inhibition assay, embelin can inhibit the acetylcholinesterase enzyme. Therefore, embelin can be utilized as a therapeutic compound, after further screening has been conducted for its use in the treatment of Alzheimer’s disease (AD). In this study, the nootropic and anti-amnesic effects of embelin on scopolamine-induced amnesia in rats were evaluated. Rats were treated once daily with embelin (0.3 mg/kg, 0.6 mg/kg, 1.2 mg/kg) and donepezil (1 mg/kg) intraperitoneally (i.p.) for 17 days. During the final 9 days of treatment, a daily injection of scopolamine (1 mg/kg) was administered to induce cognitive deficits. Besides that, behavioral analysis was carried out to assess the rats’ learning and memory functions. Meanwhile, hippocampal tissues were extracted for gene expression, neurotransmitter, and immunocytochemistry studies. Embelin was found to significantly improve the recognition index and memory retention in the novel object recognition (NOR) and elevated plus maze (EPM) tests, respectively. Furthermore, embelin at certain doses (0.3 mg/kg, 0.6 mg/kg and 1.2 mg/kg) significantly exhibited a memory-enhancing effect in the absence of scopolamine, besides improving the recognition index when challenged with chronic scopolamine treatment. Moreover, in the EPM test, embelin treated rats (0.6 mg/kg) showed an increase in inflexion ratio in nootropic activity. However, the increase was not significant in chronic scopolamine model. In addition, embelin contributed towards the elevated expression of BDNF, CREB1, and scavengers enzymes (SOD1 and CAT) mRNA levels. Next, pretreatment of rats with embelin mitigated scopolamine-induced neurochemical and histological changes in a manner comparable to donepezil. These research findings suggest that embelin is a nootropic compound, which also possesses an anti-amnesic ability that is displayed against scopolamine-induced memory impairment in rats. Hence, embelin could be a promising compound to treat AD.